Depositional changes during the Danian–Selandian transition in Loubieng (France), Zumaia (Spain) and Sidi Nasseur (Tunisia): insights from and limits of rock magnetism. (3rd May 2019) - Wouters, Sébastien; Spassov, Simo; Martinez, Mathieu; Steurbaut, Etienne; Storme, Jean-Yves; Yans, Johan; Devleeschouwer, Xavier
Abstract: Depositional changes are studied in three sections encompassing the Danian–Selandian transition, Loubieng (France), Zumaia (Spain) and Sidi Nasseur (Tunisia), using magnetic susceptibility as a proxy. Additional rock-magnetic analyses are used to avoid ambiguous interpretation of magnetic susceptibility. The magnetic susceptibility, measured on 90 to 270 samples per section, is mainly controlled by paramagnetic minerals and linked to detrital input. Major increases in the detrital input are correlated to the end of the Latest Danian Event, a hyperthermal, and to the Danian–Selandian boundary. In Loubieng, two gradual increases in magnetic susceptibility within limestones beds precede the major detrital input increases, and start synchronously with the beginning of the Latest Danian Event and the onset of haematite deposition around the Danian–Selandian boundary, respectively. This haematite is suspected to be of primary origin based, among other things, on low magnetic viscosity values, which is used here as an indicator of diagenetic origin in haematite and goethite. The red levels where haematite is interpreted to be of primary origin could be linked to the hyperthermal event previously hypothesized for the basal Selandian. The comparison of the magnetic susceptibility, chemo- and biostratigraphic data between the three sections highlights the condensed nature of the sedimentation around the Danian–Selandian boundary in the sections of the Atlantic realm. The lower part of the Selandian shows a particularly low sedimentation rate at Zumaia compared to Loubieng and Sidi Nasseur. The latter displays the most complete record of the three.